The comparison of Fennel and Mefenamic Acid effects on post-partum after pain - Sh Golian Tehrani; M Mirmohammadali; A soltani moghadam; A Mehran; M Taghizadea; M Baleghi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2015)
BACKGROUND AND OBJECTIVE: Postpartum pain and painful uterine contractions normally occur after childbirth and are regarded as one of the most common problems after delivery. Postpartum pain is significantly intensified by increased parity. Therefore, mothers are forced to use chemical drugs to inhibit this pain. Considering the side-effects of chemical drugs and the growing tendency towards herbal medicines, we aimed to compare the effects of fennel extracts and mefenamic acid on postpartum pain.